Digital Epidemiology: Using Social Media Data and Machine Learning to Forecast Influenza Outbreaks and Inform Public Health Responses - Benny Novico Zani; Ravi Raj Pandey; Le Thi Lan Anh (Journal of Social Science Utilizing Technology, 2025)
Background. Traditional influenza surveillance systems inherently suffer from a critical one-to-two-week reporting lag, severely hindering timely public health interventions and resource allocation. Purpose. This research aims to develop and validate a hybrid digital epidemiology model using unstructured social media data and advanced Machine Learning (ML) to provide accurate, long-range influenza outbreak forecasts. Method. The methodology involved quantitative time-series forecasting, training Long Short-Term Memory (LSTM) and XGBoost models on five years of social media data, and benchmarking against official clinical reports. Results. The optimized LSTM model achieved significantly superior accuracy, recording a Root Mean Square Error (RMSE) of 0.145 for the four-week forecasting horizon, less than half the error of the traditional ARIMA baseline. This high predictive power confirms that social media is a statistically reliable, non-clinical leading indicator. Conclusion. The study establishes a transparent policy translation framework, linking predicted incidence rates (e.g., exceeding 0.20) directly to required operational responses (e.g., hospital surge activation). This model offers a robust, actionable template for transforming public health surveillance from a reactive system into a proactive intelligence platform for epidemic preparedness.